Gas permeability evolution characteristics of limestone under different stress conditions. (11th November 2021) - Zhang, Qiangxing; Liu, Jianfeng; Wu, Zhide; Wang, Lu; Deng, Chaofu; Zeng, Yin
The increasing demand on energy storage has drawn worldwide attention on the construction of underground gas storage (UGS) project. As gas permeability is a key parameter in evaluating the sealing capacity of caprock in underground gas storage facilities, a comprehensive test on limestone concerning gas permeability and triaxial compression under different stress conditions was conducted using hydro-mechanical (HM) coupling testing platform in the laboratory. Also, the rock damage evolution of limestone during triaxial compression was monitored with an acoustic emission (AE) machine. Initial permeability of intact limestone ranges between 10 −18 m 2 and 10 −16 m 2 under different confining pressures, while permeability of fractured limestone is below 10 −14 m 2 . Relationships between porosity vs. confining pressure and initial permeability vs. confining pressure are negative exponential, and both porosity and initial permeability decrease with increasing confining pressure. The permeability-axial strain curves of limestone show two different evolution laws under different confining pressures, which is highly related to the crack volume deformation characteristics. Spatial localisation of AE events can accurately reflect the growth of internal cracks and explain the basic rules of permeability evolution. [Received: September 18, 2019; Accepted: November 15, 2020]